2011
DOI: 10.1083/jcb.201010104
|View full text |Cite
|
Sign up to set email alerts
|

P granules extend the nuclear pore complex environment in the C. elegans germ line

Abstract: Like the nuclear pore complex, FG repeat–containing P-granule proteins interact to help establish a size-exclusion barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
226
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(249 citation statements)
references
References 44 publications
8
226
0
Order By: Relevance
“…Hexanediol was shown to perturb FG repeat interactions between nucleoporins in nuclear pores [6] [7] and interactions between RNAbinding proteins in RNA-protein granules (RNP) [2] [8]. These studies suggested that 1,6-hexanediol interferes with weak hydrophobic protein-protein or protein-RNA interactions that are required for these dynamic, liquid-like assemblies to form.…”
Section: Resultsmentioning
confidence: 99%
“…Hexanediol was shown to perturb FG repeat interactions between nucleoporins in nuclear pores [6] [7] and interactions between RNAbinding proteins in RNA-protein granules (RNP) [2] [8]. These studies suggested that 1,6-hexanediol interferes with weak hydrophobic protein-protein or protein-RNA interactions that are required for these dynamic, liquid-like assemblies to form.…”
Section: Resultsmentioning
confidence: 99%
“…Second, because phase separated droplets are >90 % water by mass (based on protein concentrations ~300 µM), macromolecules could enter, diffuse within and exit easily. Indeed, 40 kDa dextrans readily enter P-granules in nematodes, although 155 kD dextrans are excluded (Updike et al, 2011). Together, these properties conspire to enable molecules to be concentrated within granules, but move rapidly and freely within them.…”
Section: Discussionmentioning
confidence: 99%
“…These sequences were originally identified by their similarity to those of the known prions, human prion protein and Sup35p (Gilks et al, 2004; Riejns et al, 2008; Decker et al, 2007), but also include those containing repeated G/S-F/Y-G/S motifs (Kato et al, 2012; Nott et al, 2015; Updike et al, 2011; King et al, 2012; Sun et al, 2011). These sequences can be important for targeting to, and/or formation of, RNP granules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FG repeats, a hallmark of many nuclear pore proteins, have been found in another family of P-granule proteins comprising GLH-1, -2 and -4 (Kuznicki et al, 2000). Based on these findings, P granules are considered as extensions of nuclear pore complexes (Updike et al, 2011). P granules might confer germline-specific roles on nuclear pore complexes.…”
Section: Discussionmentioning
confidence: 99%